Toolbox for power system fault analysis using MATLAB - Ismail, Mohd Fitry (2007)
Power system fault analysis is the process of determining the bus voltages and line currents during the occurrence of various types of faults. Faults on power systems can be divided into three-phase balanced faults and unbalanced faults. Three types of unbalanced fault occurrence on power system transmission lines are single line to ground faults, line to line faults, and double line to ground faults. Fault studies are used to select and set the proper protective devices and switchgears. The determination of the bus voltages and line currents is very important in the fault analysis of power system. The process consists of various methods of mathematical calculation which is difficult to perform by hand. The calculation can be easily done by computer which is generated by a program developed using MATLAB. GUI (Graphical User Interface) will be provided with the programs as they are the components of the toolbox. This user friendly toolbox will assist user which among electrical engineering student or trainee engineer to perform the fault analysis of power system